An x-ray of the puma (Puma concolor) and its environment in Chilean Patagonia : a conservation narrative about puma diet, the macro-scavengers of the steppe and livestock guardian dogs and their sheep - Reverter Perdiz, Ana (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2024)
This study provides insights into the predatory behaviour of pumas (Puma concolor), scavenger dynamics at puma-killed carcass sites, and the activity patterns of Livestock Guardian Dogs (Canis lupus familiaris) (LGDs) in the context of predator-livestock interactions in Chilean Patagonia. Using GPS collars, eight adult pumas were monitored for 16 months. I identified a predilection for targeting young guanacos (Lama guanicoe) (<1 year old) during the guanaco calving season (November-February), with predation extending up to four months post-calving. Young guanacos were most vulnerable between birth and seven months of age. Individual variations in hunting strategies were observed among pumas, emphasizing the complexity of predator behaviours. Pumas showed crepuscular hunting (n=170) and scavenging (n=51) preferences, and adult pumas were reported sharing prey’s carcasses. Camouflaging of prey carcasses by pumas prolonged feeding opportunities, although the presence of scavenger signs did not have a significant impact on feeding duration. Scavenger communities at predation sites comprised a diverse array of meso and macro species. Using camera traps, pumas, grey foxes, and southern caracaras were identified as the main scavengers in the area, with pumas and grey foxes showing the highest degree of overlap in scavenging activities. The eight pumas from the study were reported scavenging. In contrast, LGDs, monitored with GPS collars, displayed similar activity levels throughout the day and night, suggesting no pronounced increase in activity during peak puma predation hours, dusk, and dawn, although different dogs showed varying activity patterns. My findings contribute new knowledge to our understanding of puma-guanaco dynamics and scavenger ecology in agricultural landscapes in Southern Chile. My results provide valuable insights into possible conservation strategies aimed at promoting coexistence between wildlife and livestock. Further research with larger sample sizes and standardized methodologies is ...